Evaluation of the symptomatic treatment of residual neurological symptoms in Wilson disease - Hölscher, Sara; Leinweber, Barbara; Hefter, Harald; Reuner, Ulrike; Günther, Peter; Weiss, Karl Heinz; Oertel, Wolfgang H.; Möller, Jens Carsten (European neurology, 2010)
The intention of this analysis was to identify patients with treated Wilson disease (WD) and residual neurological symptoms in order to determine whether or not they were undergoing any treatment in addition to the common decoppering medication. Moreover, the effects of any symptomatic medication were analyzed. Two samples of WD patients were investigated either by a mailed questionnaire survey (n = 135) or by a retrospective analysis (n = 75). A considerable proportion of patients still suffered from neurological symptoms (n = 106, 50.5%), of whom a relatively small proportion was treated symptomatically (n = 33, 31.1%). The documented effects varied substantially, with anticholinergics and botulinum toxin (against dystonia) and primidone (against tremor) apparently being the most promising compounds. Further studies are required to analyze the symptomatic treatment of WD patients with residual neurological symptoms in more detail.